Answer:
18.8 cubic inches
Step-by-step explanation:
✔️Amount of juice Cup B will hold than Cup A = Volume of cup B - volume of cup A
✔️Volume of Cup B = Volume of cylinder = πr²h
radius (r) = ½ of 2 = 1 in.
height (h) = 7 in.
Volume of cup B = π*1²*7 = 21.99 in.³
✔️Volume of Cup A = Volume of cone = ⅓πr²h
radius (r) = ½ of 2 = 1 in.
height (h) = 3 in.
Volume of cup B = ⅓*π*1²*3 = 3.14 in.³
✔️Amount of juice Cup B will hold than Cup A = 21.99 in.³ - 3.14 in.³ = 18.8 in.³ (nearest tenth)
A acute angle is always less than 90 degrees. So the answer is A.
Answer:
Option B. Amplitude =3 midline is y =2.
Step-by-step explanation:
In the graph attached we have to find the amplitude and midline of the periodic function.
Amplitude of the periodic function = (Distance between two extreme points on y asxis)/2
= (5-(-1))/2 = (5+1)/2 =6/2 =3.
Since amplitude of this function is 3 and by definition amplitude of any periodic function is the distance between the midline and the extreme point of wave on one side.
Therefore midline of the wave function is y=2 from which measurement of the amplitude is 3.
Some definitions:
Sum - the result of adding values together
Term - a single number or variable (includes variables multiplied by numbers)
Factor - a number or variable that divides another number or expression evenly
Quotient - the result of dividing values by one another
Coefficient - a numerical or constant value often in front of a variable
In your equation:
Sum - (5x + 1)
5x and 1 are being added together, although we do not know the sum exactly, we know that the sum is equal to the value of 5 times x plus 1.
Term - (5x, 1, 3y)
All terms given above are applicable.
Factor - (9)
9 has been taken out of the expression that it is now being multiplied, which shows that it was factored out of that expression
Quotient - (9(5x + 1) / 3y)
The value of 9(5x + 1) is being divided by 3y. Though we do not know the quotient exactly, we know that the quotient is equal to the values given.
Coefficient - (5, 3)
Both 5 and 3 are numbers in front of variables.
Hope this helps!! :)
Step-by-step explanation:
2x/3 - x/3 = x/3
they both have the same denominators (number at the bottom of the fraction) so all you have to do it subtract the numerators (top of the fraction) together. 2x-x =x, that's why it's x on the numerator for the answer
hope this helps